A CRITICAL REVIEW OF THERMODYNAMIC DATA FOR SELENIUM SPECIES AT 25°C - Seby F.; Potin-Gautier M.; Giffaut E.; Borge G.; Donard O.F.X. (My University, 2001)
The accuracy of published selenium thermodynamic data was evaluated to obtain a reliable basis for modelling Se migration behaviour in contaminated areas. The Modified Bromley's Methodology was used to correct equilibrium constant to the standard state (zero ionic strength, 25°C and 1 bar pressure). Since redox reactions control the migration of selenium, equilibria between the various Se oxidation states and the associated reactions - acid-base, precipitation, and complexation - were studied.Although pKa values for H2SeO3 and H2SeO4 acid-base reactions are well known, an ambiguity exists for the second dissociation of H2Se. A value of 14 appears to be more suitable than a value close to 11.5. The most adequate standard potentials for the redox reactions of selenium are proposed. Because of the very low solubility of metal-selenides, most of their solubility product constants are derived from combination of formation thermodynamic data selected in the literature or extrapolated from those of the corresponding sulfides. Several values are reported for Se(IV) and Se(VI), but they are not always in agreement. In generally, few values have been determined recently and noticeable differences can be observed between old and recent values. For complexation reactions, there is a lack of data and for many equilibria only one constant is available.
Keywords: SELENIUM; SPECIATION; EQUILIBRIUM CONSTANTS